Prokaryotic diversity in stream sediments affected by acid mine drainage - Carlier, Jorge (2021)
The microbial communities in mining impacted areas rely on a variety of mechanisms to survive in such extreme environments. In this work, a meta-taxonomic approach using 16S rRNA gene sequences was used to investigate the prokaryotic diversity of sediment samples from water bodies affected by acid mine drainage at the Sao Domingos mining area in the south of Portugal. Samples were collected in summer and winter from the most contaminated sites from where the water flows downstream to the freshwater of Chanca's river reservoir. The prokaryotic diversity on water bodies' sediments allowed us to distinguish the highly contaminated sites (pH approximate to 2) from sites with intermediate levels of contamination (pH approximate to 3-6.5), and from sites without contamination (pH approximate to 7.5). The abundances of acidophiles of generaAcidiphilium, Acidibacter, Acidobacterium and Acidocellain the sediments were correlated with the level of acid mine drainage contamination. The two first genera were among the 30 most abundant prokaryotes in all contaminated samples, including one (SS2w), where the contamination was very diluted, thereby emphasizing the impact that such type of pollution can have in the microbial communities of sediments. In addition, the high abundances of archaeal taxa from classThermoplasmataand of bacteria from family RCP1-48 in the sediments from the most contaminated site corroborate their importance in such ecosystems and a putative role in the generation of acid mine drainage.